Histomorpholgical Studies on the Gall Bladder of Sheep During Prenatal and Postnatal Development - Choudhury, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on gall bladder of embryo/fetuses (n= 30) of 18 days’ old (0.40 cm whole embryo length WEL) to postnatal sheep (n=10) below one year of age without any external anomaly to investigate the histomorphological changes during prenatal and postnatal development. The prenatal gall bladders were divided into three groups comprised of ten samples in each group according to the gestational age viz. Group I (0-50), Group II (51-100), Group III (101-150) days of gestation and Group IV comprised of sheep below one year of age. A progressive increase in length and width of gall bladder and length and diameter of cystic duct were observed both in prenatal and postnatal periods with advancing age. At 18 days of gestation (0.40 cm WEL) gall bladderprimordia appeared as an elongated sac present caudal to the hepatic bud under the fore gut. At 29.50 days of gestation (1.30 cm WEL) gall bladder had a narrow lumen and a thin layer of undifferentiated mesenchymal cells organized around it. Few small sized mucosal diverticulae extending for a variable depth into the underlying lamina propria and lined with the cells closely resembling the surface epithelium were also observed. The surface of the gall bladder in contact with the liver was lined by adventitia and mesothelium was absent. There was apositive correlation between thickness of epithelium, propria submucosa, tunica muscularis and tunica serosa of gall bladder with increase in gestational age and post-I natal development.